(untitled) (Architecture Image Studies, 2025)
The quality of the educational and physical environment is one of the factors that greatly affects the mental health and adaptability of students, especially gifted students who have many special cognitive and emotional needs. Despite the numerous studies that have addressed the educational environment or psychological variables among students, research on the integrative relationship between the quality of the spatial environment, psychological immunity, and positive coping strategies among gifted students remains scarce in the Arab context, especially among gifted students in Saudi society. Therefore, the current study aimed to examine the relationship between the quality of the educational and spatial environment, psychological resilience, and positive coping strategies among gifted students in southern Saudi Arabia, while analyzing the mediating role of psychological resilience in explaining the relationship between the spatial environment and positive coping. A descriptive correlational approach with a cross-sectional design was used. The study sample consisted of 320 gifted students. Three scales were used to measure the variables, and the data were analyzed using descriptive statistics, Pearson’s correlation coefficient, and structural equation modeling (SEM). The results of the study indicated an increase in the arithmetic means of all variables, and found positive and statistically significant correlations between the quality of the educational environment and psychological resilience, and between psychological resilience and positive coping strategies. The SEM model also confirmed a direct effect of environmental quality on positive coping, in addition to an indirect effect through psychological resilience, indicating partial mediation. The results also indicated that there were no significant differences between cities or genders, while differences in favor of high school students were found in psychological resilience. The results of the current study emphasize the need to design school environments that provide good psychological and normative support, and to develop programs that promote psychological resilience and positive coping. Further longitudinal and objective studies are recommended to interpret causal relationships more accurately.